USING AUDIO-VISUAL MEDIA IN THE FORM OF LEARNING VIDEO TO IMPROVE THE LISTENING ABILITY OF THIRD-GRADE STUDENTS OF SMP NEGERI 4 MENGKENDEK - Kala'allo, Teresia Octavia; Talib, Ahmad; Muliati M, A. (Universitas Negeri Makassar, 2022)
This pre-experimental research aims to identify whether using audio-visual media in the form of learning videos can improve the listening ability of third-grade students of SMP Negeri 4 Mengkendek. The released fickle in this research is a learning video while the contingent fickle listens to ability. The inhabitant in this investigation was every third-grade learner of SMP Negeri 4 Mengkendek, as many as 5 classes, while the sample was class III. A with 20 students. The research instrument used a listening test; the test given to students consisted of 2, namely a pre-test and a post-test consisting of 30 multiple-choice questions. The data analysis technique is SPSS, built on the proceeds of data coverage, P = 0.001 is smaller than ɑ= 0.05, which means that H0 of this study is refused and H1 is received. So, it should be decided that the application of learning using audio-visual learning videos improves the listening ability of third-grade students of SMP Negeri 4 Mengkendek.